Prototype Sistem Deteksi Partial Discharge Pada Isolasi Kabel Menggunakan Sensor Microphone - Mochamad Zaeynuri Setiawan; Fachrudin Hunaini; Mohamad Mukhsim (Muhammadiyah University, Sidoarjo, 2019)
The phenomenon that often arises in a substation is the problem of partial discharge in outgoing cable insulation. Partial discharge is a jump of positive and negative ions that are not supposed to meet so that it can cause a spark jump. If a partial discharge is left too long it can cause insulation failure, the sound of snakes like hissing and the most can cause a flashover on the outgoing cable. Then a partial discharge detection prototype was made in the cable insulation in order to anticipate the isolation interference in the outgoing cable. Can simplify the work of substation operators to check the reliability of insulation on the outgoing side of each cubicle. So it was compiled as a method for measuring sound waves caused by partial discharge in the process of measuring using a microphone sensor, the Arduino Mega 2560 module as a microcontroller, the LCD TFT as a monitoring and the MicroSD card module as its storage. The microphone sensor is a sensor that has a high sensitivity to sound, has 2analog and digital readings, and is easily designed with a microcontroller. Basically the unit of measure measured at partial discharge is Decibels. The results of the prototype can be applied to the cubicle and the way it works is to match the prototype to the outgoing cubicle cable then measure from the cable boots connector to the bottom of the outgoing cable with a distance of 1 meter. Then the measurement results will be monitored on the TFT LCD screen in the form of measurement results, graphs and categories on partial discharge. In this design the measurement data made by the microphone can be stored with microSD so that it can make an evaluation of partial discharge handling in outgoing cable insulation.